Dislocation analysis of a complex sub-grain boundary in UO2 ceramic using accurate electron channelling contrast imaging in a scanning electron microscope. Issue 15 (15th October 2019) - Mansour, H.; Crimp, M.A.; Gey, N.; Iltis, X.; Maloufi, N.
Abstract: In this work, accurate electron channelling contrast imaging (A-ECCI) assisted by high resolution selected area channelling patterns (HR-SACP) was used to characterize the structure of a complex low sub-grain boundary in a creep deformed uranium dioxide (UO2 ) ceramic. The dislocations were characterized using TEM-styleg ·b  = 0 andg ·b  × u  = 0 contrast criteria. Misorientations across the boundary were measured using HR-SACPs with 0.04° precision and high accuracy EBSD. The boundary was determined to be asymmetric and mixed in nature, composed of two distinct regions with different dislocation morphologies and a misorientation below 0.5°. The A-ECCI, HR-SACP, and HR-EBSD results are consistent, confirming A-ECCI as a powerful tool for characterizing even complex dislocations structures using scanning electron microscopy. This is particularly true for UO2, since this material is very difficult to thin, which makes TEM examination of sub-boundaries over the scale of several micrometers difficult. Furthermore, in this study, the change in dislocations arrangement along the breath of the complex low angle sub-grain boundary is related to the misorientation across the boundary.